Evaluation of Wireless Sensor Networks Technologies - Salan Padillo, Ignacio (Cranfield University, 2008)
Wireless sensor networks represent a new technology that has emerged from developments in ultra low power microcontrollers and sophisticated low cost wireless data devices. Their small size and power consumption allow a number of independent ‘nodes’ (known as Motes) to be distributed in the field, all capable of ad-hoc networking and multihop message transmission. New routing algorithms allow remote data to be passed reliably through the network to a final control point. This occurs within the constraints of low power RF transmissions in a congested 2.4GHz radio spectrum. Wireless sensor network nodes are suitable for applications requiring long term autonomous operation, away from mains power supplies, such as environmental or health monitoring. To achieve this, sophisticated power management techniques must be used, with the units remaining ‘asleep’ in ultra low power mode for long periods of time. The main aim of this research described in this thesis is first to review the area and then to evaluate one of the current hardware platforms and the popular software used with it called TinyOS. Therefore this research uses a hardware platform designed from University of Berkeley, called the TmoteSky. Practical work has been carried out in different scenarios. Using Java tools running on a PC, and customized applications running on the Motes, data has been captured, together with information showing topology configuration and adaptive routing of the network and radio link quality information. Results show that the technology is promising for distributed data acquisition applications, although in time critical monitoring systems new power management schemes and networking protocols to improve latency in the system will be required.